Dataset for "Outperforming yet undervalued: undergraduate women in STEM" - Bloodhart, Brittany (Colorado State University. Libraries, 2018)
Gender diversity is critically needed in many science fields, but women continue to encounter beliefs that they lack ability and talent. Undergraduate education is a critical time when peer influence may alter choice of majors and careers for women interested in science. Even in life science courses, where women outnumber men, peer-to-peer interactions could detract from women's success and interest. We find that women are outperforming their male classmates in both physical and life science courses, but men continue to be perceived as equal or better students. This is problematic because it suggests that undergraduate women cannot escape gender-ability stereotypes even when they are more capable than men, and has important implications for the recognition of women's achievements among their peers in undergraduate education.
Undergraduate students' academic performance and perceptions of classmates.
The dataset consists of a single (.csv) data file containing anonymous student data for 2793 students. Variables are defined below and in the accompanying codebook. This data is reported in the manuscript: "Outperforming yet undervalued: Undergraduate women in STEM." There are 3 total files included in this database: 1. This README file which gives an overview of the data 2. The data file (.csv file) 3. The codebook, which describes each variable in the data file, coding values, and additional information on each measure.
Department of Atmospheric Science
Keywords: undergraduate STEM; women in STEM; gender bias